2015
DOI: 10.1177/230949901502300211
|View full text |Cite
|
Sign up to set email alerts
|

Single-Door Cervical Laminoplasty Using Titanium Miniplates Alone

Abstract: Purpose. To review outcome of 29 patients who underwent single-door cervical laminoplasty for myelopathy using titanium miniplates alone. Methods. Records of 20 men and 9 women aged 35 to 79 (mean, 64.3) years who underwent single-door cervical laminoplasty for myelopathy using titanium miniplates alone were reviewed. A total of 125 laminae were opened; 97 of them were fixed with a titanium miniplate. In 19 patients, a 20-hole titanium miniplate bent to the contour of a lamina was used and fixed into 3 laminae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…The normal cervical aging process, congenital narrowing aggravated by acute trauma and bony malformations were identified as the primary causes of cervical stenosis that result in myelopathy. [1][2][3][4][5] Titanium miniplates fixation can be used to instantly reconstruct the spinal canal to restore its integrity. A relatively stable mechanical environment is conducive to bone slot healing on the door axial side and is also conducive to left and right muscle strength balance in the neck.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The normal cervical aging process, congenital narrowing aggravated by acute trauma and bony malformations were identified as the primary causes of cervical stenosis that result in myelopathy. [1][2][3][4][5] Titanium miniplates fixation can be used to instantly reconstruct the spinal canal to restore its integrity. A relatively stable mechanical environment is conducive to bone slot healing on the door axial side and is also conducive to left and right muscle strength balance in the neck.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining ventral cortex and the ligamentum flavum were removed using a diamond burr and Kerrison rongeur. 1,5 The precontoured laminoplasty system was used and fixed into 3, 4, 5 laminae. Care was taken to avoid breaking the hinge.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Various materials are used to maintain the enlarged spinal canal such as thread 3) , autogeneous bone (spinous process 4,5) , iliac bone 2,6) ), hydroxyapatite spacer [7][8][9][10][11][12][13][14][15][16][17] , and titanium plate and screw 18,19) . Double-door type was first developed by Kurokawa in the late 1970s and reported in 1982 2) .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been modified because of complications such as postoperative axial symptoms (post-AS) [4,5], laminar reclosure [6], reduced range of neck motion [7], and C5 palsy [8]. Titanium miniplate fixation is a modified laminoplasty (ML) that provides immediate and rigid fixation with satisfactory clinical outcomes [9]. Yeh et a.l [10] also demonstrated that laminoplasty using titanium miniplates is a safe and effective surgical alternative to CSM.…”
Section: Introductionmentioning
confidence: 99%